Autophagy participates in cyst breakdown and primordial folliculogenesis by reducing reactive oxygen species levels in perinatal mouse ovaries. Issue 5 (24th September 2018) - Zhihan, Tu; Xinyi, Mu; Qingying, Li; Rufei, Gao; Yan, Zhang; Xuemei, Chen; Yanqing, Geng; Yingxiong, Wang; Junlin, He
Abstract: The reserve of primordial follicles, which serves all oocytes for the female reproductive lifespan, is established a few days after birth in mice. During this process, more than half of the oocytes are primarily eliminated by apoptosis. Autophagy, the conserved intracellular process maintaining cellular homeostasis, serves as a protective mechanism for oocyte survival. In the current study, we speculate a new role for autophagy during primordial folliculogenesis. Active autophagy was observed in perinatal ovaries from 16.5 days post coitus to 3 days post parturition. The inhibition of autophagy by 3‐methyladenine (3‐MA) increased the number of cyst oocytes and delayed follicle formation in vivo and in organ cultures. Furthermore, the reactive oxygen species (ROS) level was elevated in ovaries treated with 3‐MA, while N ‐acetylcysteine, an oxidant, alleviated the inhibitory effect of 3‐MA on primordial folliculogenesis. Additionally, the expression of growth differentiation factor 9 and transforming growth factor β1, which regulates follicle activation, was decreased after 3‐MA treatment. These data suggest that the physiological level of autophagy in perinatal ovaries regulates germ cell cyst breakdown and primordial follicle assembly by ROS clearance and exerts extensive effects on further follicular development. Abstract : Active autophagy was observed in perinatal ovaries from 16.5 dpc to 3 dpp, and the physiological level of autophagy in perinatal ovaries regulates germ cell cyst breakdown and primordial follicle assembly by ROS clearance and exerts extensive effects on further follicular development.